FACTORS RELATED TO THE INCIDENCE OF MUSCULOSKELETAL DISORDERS (MSDSS) IN CONVECTION X HOME INDUSTRY WORKERS IN SOUTH TANGERANG CITY IN 2023 - Ghafira Nisa Ramadhanti; Azizah Zen; Andriyani; Ernyasih (Muhammadiyah International Public Health and Medicine Proceeding, 2024)
Disorders affecting bones, joints, muscles, tendons, ligaments, and nerves are referred to as musculoskeletal disorders (MSDs). Around the world, musculoskeletal disorders (MSDs) account for 17% of Years Lived Disability (YLD). The purpose of this study was to identify the variables associated with the prevalence of MSDs. Thirty convection workers made up the sample for this cross-sectional study. Nordic Body Map questionnaires and REBA (Rapid Entire Body Assessment) measurement observation sheets are used in this study's data collection method. A final REBA score of 5 was obtained from the pattern and sewing stages, indicating that the situation is at medium risk and requires improvement. This condition needs to be improved right now because the last stage findings yielded a final REBA score of 3, which indicates that it is low risk. According to REBA's evaluation, five respondents (16.7%) were at a high-risk level, whereas 23 respondents (76.7%) were at a moderate-risk level. According to MSD complaints, all employees (36.7%) had minor concerns, while 63.3 percent had moderate problems. The incidence of MSDs was correlated with age (p value=0.000), working period (p value=0.000), physical activity (p value=0.009), and work posture (p value=0.041). There was no correlation between smoking habits and the incidence of MSDs (p value=0.425) or between sex and the incidence of MSDs. According to the REBA data, there is a moderate amount of risk (76.7%) associated with the worker's posture. Musculoskeletal disorders (MSDs) were moderately prevalent (63.3%) in the NBM assessment. Numerous people mentioned complaints regarding their right shoulders, buttocks, waists, and backs. To meet the nutritional demands of employees who work longer shifts, there is a necessity for relaxation or stretching for one to two hours during or after work.